PENGARUH LAMA FERMENTASI TERHADAP KARAKTERISTIK, KANDUNGAN PROTEIN DAN SERAT KASAR TONGKOL JAGUNG - Tintin Rostini; Achmad Jaelani; Muhammad Ali (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Corn cobs are agricultural waste that is easy to obtain because the waste has not been optimally utilized. The waste has the potential to be used as feed for livestock, but has a low quality. The purpose of this study was to determine the characteristics, protein content and crude fiber of corn cobs with different fermentation times. The research method used a completely randomized design (CRD), with five treatments. The length of fermentation consisted of 0.5.10.15 and 20 days and was repeated 4 times so that there were 20 experimental units. The results of the study The length of fermentation on corn cobs can increase the characteristic value, increase protein content and can reduce the crude fiber content of corn cobs so that it is easier for livestock to digest.